'We All Have a Responsibility to Each Other': Valuing Racialised Bodies in the Neoliberal Bioeconomy. Issue 5 (3rd September 2018) - Merz, Sibille; Williams, Ros
ABSTRACT: In neoliberalism, human tissue has been targeted as a source for extracting surplus value. Commercial attention on ethnic and racial minorities has resulted in products and services specifically developed for them. Here, we focus on this by exploring two empirical examples: US pharmaceutical clinical trials and UK stem cell transplantation. Both use racial taxonomies to discern biological difference and draw conclusions about the economic potential of people's genetic constitutions. They do so by appealing to racialised minorities' sense of responsibility towards 'their' communities, both buttressing the conflation of social and biological registers of human variation and demonstrating neoliberalism's mobilisation of discourses of community. However, while the inclusion of racialised minorities is hoped to bring economic benefits, it also aims to address healthcare inequalities. Drawing on Science and Technology Studies, we argue that in our examples, economic, social and cultural values cannot be disentangled. This compels us to complement narratives of the commodification of racialised difference in neoliberal (consumer) culture, and focus on the intersections between different economic and ethical values. Ultimately we find that whilst work is being done to ameliorate racial inequities, broader socio-economic and political inequalities minority communities face go unaddressed, likely precluding the realisation of health equality.